Validation of the Brazilian version of Behavioral Pain Scale in adult sedated and mechanically ventilated patients - Isabela Freire Azevedo-Santos (Revista Brasileira de Anestesiologia)
Abstract Background and objectives: The Behavioral Pain Scale is a pain assessment tool for uncommunicative and sedated Intensive Care Unit patients. The lack of a Brazilian scale for pain assessment in adults mechanically ventilated justifies the relevance of this study that aimed to validate the Brazilian version of Behavioral Pain Scale as well as to correlate its scores with the records of physiological parameters, sedation level and severity of disease. Methods: Twenty-five Intensive Care Unit adult patients were included in this study. The Brazilian Behavioral Pain Scale version (previously translated and culturally adapted) and the recording of physiological parameters were performed by two investigators simultaneously during rest, during eye cleaning (non-painful stimulus) and during endotracheal suctioning (painful stimulus). Results: High values of responsiveness coefficient (coefficient = 3.22) were observed. The Cronbach's alpha of total Behavioral Pain Scale score at eye cleaning and endotracheal suctioning was 0.8. The intraclass correlation coefficient of total Behavioral Pain Scale score was ≥ 0.8 at eye cleaning and endotracheal suctioning. There was a significant highest Behavioral Pain Scale score during application of painful procedure when compared with rest period (p ≤ 0.0001). However, no correlations were observed between pain and hemodynamic parameters, sedation level, and severity of disease. Conclusions: This pioneer validation study of Brazilian Behavioral Pain Scale exhibits satisfactory index of internal consistency, interrater reliability, responsiveness and validity. Therefore, the Brazilian Behavioral Pain Scale version was considered a valid instrument for being used in adult sedated and mechanically ventilated patients in Brazil.